PERAN PEMERINTAH KOTA MALANG DALAMM MENGEMBANGKAN RUANG TERBUKA HIJAU DENGAN PENDEKATAN KONSEP COLLABORATIVE GOVERNANCE - Rossy Rahmawati; Mas’ud Said; Retno Wulan Sekarsari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to provide an understanding of the Malang City Government's efforts to develop green open space with a collaborative governance approach. This research includes an understanding of the central role of government, green open space conditions, collaborative governance strategies, and sustainability steps taken in the context of green open space development in Malang City. Green Open Space (RTH) is a structure in the city that supports the city's ecology as an improvement in the quality of the environment in Malang City. The development of green open space in the past month has reached its maximum point with all its problems starting from planning for green open space development which often fails and is diverted into trading land and is less effective. green open space management. The research uses a descriptive qualitative method which focuses on the role of the Malang City government in the development and development of green open spaces in Malang City which is analyzed from a collaborative governance perspective. The results of the research show that there is collaboration between the city government and the community and the private sector in the development of green open space, however, there are still shortcomings in its implementation, such as the role of the community as outlined through the Musrenbang RKPD which has been carried out but in the end the development of green open space is said to be far from the community's expectations, then it was discovered There are also deficiencies in the management and development of RTH that are not on target.